Permodelan Hidrologi Daerah Aliran Sungai Sengkarang Kabupaten Pekalongan Dengan Perangkat Lunak HEC-HMS - Angsa Dilaguna Biru; Tamara Budi A; Budi Santosa (Universitas Katolik Soegijapranata Semarang, 2018)
Along with the increase of human population, the necessity of housing will increase as well. Therefore land use change cannot be avoided. Land use change on watersheds (DAS) is one of the causes of flood. The purpose of this study is to examine the changes of hydrograph on watersheds caused by land use change within 20 years. The data used in the form of rainfall data in 2011-2016, land use maps in 2011 and 2031 and topographic maps of soil types. Using HEC-HMS software will be obtained the results of 2011 and 2031 river flow hydrograph. The results of this modeling were compared to find out the Peak Discharge at weir Ps. Kletak. In 2-year return period of 2011 and 2031 are 662,6 m3/s and 770,8 m3/s with increase 16.33%, and for a 50-year return period of 2011 and 2031 are sebesar 1643,2 m3/s dan 1774,2 m3/s with increase 7.97%.